Effect of vertical sleeve gastrectomy in melanocortin receptor 4-deficient rats - Joram D. Mul; Denovan P. Begg; Suzanne Alsters; Gijs van Haaften; Karen Duran; David A. D’Alessio; Carel W. le Roux; Stephen C. Woods; Darleen A. Sandoval; Alexandra I. F. Blakemore; Edwin Cuppen; Mieke M. van Haelst; et al. (2012)
Bariatric surgery is currently the most effective treatment for obesity. Vertical sleeve gastrectomy (VSG), a commonly applied bariatric procedure, involves surgically incising most of the volume of the stomach. In humans, partial loss of melanocortin receptor-4 ( MC4R) activity is the most common monogenic correlate of obesity regardless of lifestyle. At present it is unclear whether genetic alteration of MC4R signaling modulates the beneficial effects of VSG. Following VSG, we analyzed body weight, food intake, glucose sensitivity, and macronutrient preference of wild-type and MC4R-deficient ( Mc4r +/− and Mc4r −/− ) rats compared with sham-operated controls. VSG reduced body weight and fat mass and improved glucose metabolism and also shifted preference toward carbohydrates and away from fat. All of this occurred independently of MC4R activity. In addition, MC4R was resequenced in 46 human subjects who underwent VSG. We observed common genetic variations in the coding sequence of MC4R in five subjects. However, none of those variations appeared to affect the outcome of VSG. Taken together, these data suggest that the beneficial effect of VSG on body weight and glucose metabolism is not mediated by alterations in MC4R activity.